Focusing on discoidin domain receptors in premalignant and malignant liver diseases - Gong, Hang; Xu, Hui-Mei; Zhang, De-Kui (Frontiers in Oncology, 2023)
Discoidin domain receptors (DDRs) are receptor tyrosine kinases on the membrane surface that bind to extracellular collagens, but they are rarely expressed in normal liver tissues. Recent studies have demonstrated that DDRs participate in and influence the processes underlying premalignant and malignant liver diseases. A brief overview of the potential roles of DDR1 and DDR2 in premalignant and malignant liver diseases is presented. DDR1 has proinflammatory and profibrotic benefits and promotes the invasion, migration and liver metastasis of tumour cells. However, DDR2 may play a pathogenic role in early-stage liver injury (prefibrotic stage) and a different role in chronic liver fibrosis and in metastatic liver cancer. These views are critically significant and first described in detail in this review. The main purpose of this review was to describe how DDRs act in premalignant and malignant liver diseases and their potential mechanisms through an in-depth summary of preclinical in vitro and in vivo studies. Our work aims to provide new ideas for cancer treatment and accelerate translation from bench to bedside.